The Influence of Training and Career Development on Employee Job Satisfaction - Firgan Mulyadi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
A high target has always been the orientation of almost all companies because it will make the company progress and develop, so the company must create employee job satisfaction so that the employee can work optimally and accelerate what is the company's orientation. Career Training and Development is an important factor of course within the company because it is a motivating factor for employees to be able to make the company progress and develop. This research aims to assist PT Kartika Inti Sejati in realizing its future desires in achieving its vision and mission through employee job satisfaction. The research method used is a quantitative research method with descriptive analysis and path analysis. The object of this research is employees who have participated in training and career development at PT Kartika Inti Sejati, with a population of forty-seven respondents. Based on the results of this study it can be concluded that there is an effect of training on employee job satisfaction, career development on employee job satisfaction, and there is an effect of training and career development on employee job satisfaction and while the influence of other remaining factors that are not examined.